The writing life : writers on how they think and work : a collection from the Washington post book world / Marie Arana (Writer) - Arana, Marie
Presents reprints of articles by over fifty professional authors in which they discuss aspects of their lives as writers, drawn from throughout ten years of the "Writing Life" column of the "Washington Post."